ANALISIS KELAYAKAN USAHATANI DURIAN DI DESA PAKISAN KECAMATAN TLOGOSARI ( Study Kasus Di Desa Pakisan Kec. Tlogosari Kab. Bondowoso ) - Adhitya Yazi Adam; Martono Achmar (Program Studi Agribisnis Fakultas Pertanian, 2015)
The research was determined the durian farm income each of year in the village of Pakisan District of Tlogosari Regency of Bondowoso, knowing how feasibility durian farm in the village of Pakisan District of Tlogosari Regency of Bondowoso. Statistical analysis used is descriptive method. Descriptive method is a method used to depict or describe the data in a systematic, factual, and accurate about the facts - facts and relationships between phenomena that are looking for. The sampling technique by means of a simple random and each respondent has an equal chance of being sampled. Durian farmers overall population (productive and non-productive) harvest season in 2014 in the village of Pakisan there are 123 farmers. But durian farmers productive population by 30 farmers so that sampling techniques into census technique which makes all the productive population durian farmers into a sample of 30 farmers. The results showed that the durian farm income during the first year by the farmers in the village of Pakisan District of Tlogosari Regency of Bondowoso profitable, where durian farm income earned average - average in the period of 1 year to reach Rp. 18.9569 million, and durian farm in the village of Pakisan District of Tlogosari the regency of Bondowoso feasible to try, prospects of this farm has a good chance to be developed further. Where the average per year for the feasibility of a durian farm in the village of Pakisan which was analyzed by B / C ratio is 13.47 and for the calculation of B / C Ratio durian farm on average reaches 1.15 per month. Suggestions of researchers is In durian farming activities in the village of Pakisan District of Tlogosari, farmers must be active and diligent in working in the field of durian cultivation and if necessary can be improved by adopting a more modern agricultural technologies in order to produce agricultural products such as durian high quality and good quality that can increase the income of farmers themselves